Legal epistemology and the keys to democracy - Caviglia Marconi, Alessandro (2015)
This work aims to show in what way the shift to the epistemology that has taken place in the philosophy of law, due to the influence that legal positivism has had during the last century and a half, has produced a disconnection between said discipline and political philosophy, creating important consequences, both in the comprehension and the practice of law. The major of these consequences is that law has become a discipline isolated from the rest of the practical disciplines,and the legal practice has been separated from the democratic proceedings and the deliberative. If the legal epistemology accepts the pragmatic shift suggested, in its moment, by Oliver Holmes, it will be possible to reverse this situation and law will be able to connect again with democratic practices.